2014
DOI: 10.1016/j.jmb.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the GerD Spore Germination Protein of Bacillus Species

Abstract: Spore germination in Bacillus species represents an excellent model system with which to study the molecular mechanisms underlying the nutritional control of growth and development. Binding of specific chemical nutrients to their cognate receptors located in the spore inner membrane triggers the germination process that leads to a resumption of metabolism in spore outgrowth. Recent studies suggest that the inner membrane GerD lipoprotein plays a critical role in the receptor-mediated activation of downstream g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Similarly, insertions in the gerK operon were largely absent in the Δ4 gerK + library. Consistent with the idea that the germinant receptors do not work with pathway‐specific signaling proteins that are critical for germination (Li et al ., ), there were no additional genes in which transposons were specifically under‐represented in one but not the other library. However, examination of the transposon insertion profiles identified an unanticipated set of genes in which insertions were over‐represented in the Δ4 gerK + library compared to the wild‐type and Δ4 gerA + libraries (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, insertions in the gerK operon were largely absent in the Δ4 gerK + library. Consistent with the idea that the germinant receptors do not work with pathway‐specific signaling proteins that are critical for germination (Li et al ., ), there were no additional genes in which transposons were specifically under‐represented in one but not the other library. However, examination of the transposon insertion profiles identified an unanticipated set of genes in which insertions were over‐represented in the Δ4 gerK + library compared to the wild‐type and Δ4 gerA + libraries (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Unfortunately, there are no data on the precise conditions in this compartment of sporulating cells. GerD is a helical trimer in vitro and may be capable of forming even higher-order oligomeric structures (11). In addition, GerD-GFP can form germinosome-like foci in dormant spores even in the absence of GRs (9).…”
Section: Figmentioning
confidence: 99%
“…Spores lacking GerD germinate normally with nonnutrient germinants that bypass the GRs, suggesting that GerD is required for efficient signal transduction from the nutrient-GR complex; however, the exact signaling mechanism remains unknown (10). The crystal structure of two-thirds of Geobacillus stearothermophilus GerD was solved recently, and the protein forms a rod-like trimer that is largely hydrophilic with a hydrophobic lipid anchor (11). Interestingly, a previous study as well as very recent work indicate that levels of GerD decrease markedly in the IM fraction from germinating and early outgrow-ing spores, suggesting that the protein becomes soluble or is degraded during this period (12,13).…”
mentioning
confidence: 99%
“…So far, the exact functions of the individual GR subunits and their interactions have not been elucidated (12). GRs are thought to cluster in complexes, so-called germinosomes, involving the GerD lipoprotein that influences GR-dependent germination rates (16,17) and possibly the SpoVA channels (located in the spore inner membrane) that are involved in the release of small molecules, mainly dipicolinic acid (DPA) and monovalent cations, and uptake of water during germination (12). Recently, it was shown that heat resistance and the germination rate of B. subtilis spores could be attributed to the number of spoVA 2mob copies on the genome, with a higher number of copies (up to three) correlating with increased heat resistance and reduced germination rate (18,19).…”
mentioning
confidence: 99%